2015
DOI: 10.1080/09670874.2015.1028510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prophylactic sprays on pest abundance, foliar damage and yield in winter wheat

Abstract: Producers in the Mid-Atlantic region of the United States often use prophylactic pesticide sprays in their fields to increase wheat (Triticum aestivum L.) yields regardless of disease or insect pest levels. This study was carried out at two sites during each of two field seasons to evaluate th-e effects of pesticide applications (fungicides and insecticide) on insect abundance, beneficial arthropods, foliar damage and grain yield in winter wheat. Insecticide applications reduced densities of cereal leaf beetle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In small cereals, aphids are important insect-pests often correlated with FHB severity, but the efficacy of insecticide application seems strongly related to pest pressure. While, prophylactic sprays with insecticides will not enhanced wheat yields in absence of high pest pressure [291], in Indian trials the application at heading significantly improved FHB control, but no data were collected on mycotoxin [292]. Further, in Northern Europe the use of insecticides in cereals showed a low effect, although significant, with the infestation by F. graminearum and the consequent mycotoxins [286].…”
Section: Fusarium Disease and Toxins Managementmentioning
confidence: 99%
“…In small cereals, aphids are important insect-pests often correlated with FHB severity, but the efficacy of insecticide application seems strongly related to pest pressure. While, prophylactic sprays with insecticides will not enhanced wheat yields in absence of high pest pressure [291], in Indian trials the application at heading significantly improved FHB control, but no data were collected on mycotoxin [292]. Further, in Northern Europe the use of insecticides in cereals showed a low effect, although significant, with the infestation by F. graminearum and the consequent mycotoxins [286].…”
Section: Fusarium Disease and Toxins Managementmentioning
confidence: 99%
“…For instance, an experiment that took place during 2008-2009 revealed that cereal aphid densities were not reduced by treatment with the pyrethroid insecticide lambda-cyhalothrin. However, when the same experiment was repeated during 2010-2011, the same insecticide killed the exposed aphids [253]. This fact could be attributed to the high precipitation levels occurring in 2008-2009 vs. 2010-2011 [253].…”
Section: Effect Of Agricultural Practices and Environmentmentioning
confidence: 97%
“…However, when the same experiment was repeated during 2010-2011, the same insecticide killed the exposed aphids [253]. This fact could be attributed to the high precipitation levels occurring in 2008-2009 vs. 2010-2011 [253]. The efficacy of insecticides may differ among strains of the same aphid species.…”
Section: Effect Of Agricultural Practices and Environmentmentioning
confidence: 99%
“…There has been much progress in identifying the impact of pesticides on non-target beneficial organisms, such as through the International Organization for Biological Control (IOBC), who develop standard methods (ranging from laboratory through to field experiments) for testing the side effects of pesticides on natural enemies [ 6 ]. Despite this knowledge, there is still reluctance by the majority of farmers to use alternatives to broad-spectrum pesticides [ 7 , 8 ]. This situation is certainly true in Australia, particularly in the grains industry, which is one of the largest primary industries, with exports worth almost AU$6 billion annually and over 35 million ha planted each year [ 9 ].…”
Section: Introductionmentioning
confidence: 99%